PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUKASI MATEMATIS SISWA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Elis Hana Solihat; Eka Senjayawati; Nelly Fitriani; Tupa Minokti (IKIP Siliwangi, 2023)
The purpose of this study was to examine students' mathematical communication skills which included the material of Single Variable Linear Equation (PLSV) using a contextual approach. The type of research used is Classroom Action Research (CAR) with the subject of this research are 15 students of class VII-D in one of the public junior high schools in Cimahi city in the even semester of 2021-2022 which has a Minimum Completeness Criteria (KKM) value of 7.00. The data collection technique was carried out by conducting an initial test which was carried out before the action (pre-test), then doing the first cycle test and the second cycle which was carried out after giving the action (post-test), each cycle was carried out in 2 meetings. From each of the test questions, the results obtained that aspects of students' mathematical communication skills always increased from each cycle. Based on the data obtained in the initial pre-test there were 26.7%, the first cycle was 40%, there was an increase in the second cycle, namely 86.67% of students who completed. The conclusion of this study is that the mathematical communication skills of seventh grade junior high school students using a contextual approach can be improved.